POTENSI DAUN TEH HIJAU (Camellia sinensis) SEBAGAI INHIBITOR MAIN PROTEASE (Mpro) COVID-19: SEBUAH STUDI MOLECULAR DOCKING - Haidar Ali Hamzah; Junoretta Haviva Ernanto; Putri Mahirah Afladhanti; Theodorus Theodorus (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Green tea is an herbal plant that has active compounds including anti-inflammatory, antioxidant, anti-allergic, and antiviral compounds. A previous study, flavonoid compound in tea leaves has been proven as antiviral. The development of effective antiviral drugs against COVID-19 remains a challenge for researchers across the world. A previous study investigated the role of the main protease enzyme (Mpro) which is useful in the viral life cycle as a promising drug target. This study aims to know the potential compounds of green tea leaves as a COVID-19 Mpro inhibitor using molecular docking. 12 compounds and lopinavir were used. Lipinski analysis was carried out to assess potential compounds as a drug. Docking was carried out by Autodock Tools 1.5.6 and Autodock Vina. The visualization was carried out by Discovery Studio v16. The results showed that all compounds compiled the criteria as a drug based on Lipinski rules. Catechin and epicatechin have the same energy bond as lopinavir with a binding energy of -7.1 kcal/mol. Catechin gallate and epicatechin gallate have the strongest energy bond with a binding energy of -9.0 and -8.2 kcal/mol. All compounds bind in the active site of the COVID-19 Mpro so they are competitive inhibitor. Catechin gallate is the strongest inhibitors.